System-wide assessment of plastic pollution in Indonesia: external stakeholder mapping - Spyridoula Gerassimidou; Mike Webster; Andre Kuncoroyekti; David C. Wilson; Susan Jobling; Eddy Soedjono; Elena Lovat; Eleni Iacovidou (Environment Systems and Decisions, 2025)
Recent global initiatives, such as the Global Plastics Treaty, highlight the urgency for a systems-based approach to address the risks associated with plastic pollution. However, the implementation of such initiatives is often hindered by the absence of clear criteria for what constitutes a systemic approach and who is included within it. This study offers a comprehensive analysis of external stakeholders, those who are not directly engaged in the physical flow of plastics, contrasted with internal stakeholders, who play direct roles in the physical production, consumption and waste generation and management. While internal stakeholders have traditionally received increased attention in value chain studies, external stakeholders remain largely overlooked. To address this gap, this research introduces a novel approach, embedded in the systems-based method, called Complex Value Optimisation for Resource Recovery (CVORR), to identify, map and categorise external stakeholders in the plastics value chain in Banyuwangi, Indonesia, based on organisation type, activities, and interest. The study reveals a complex system of 111 external stakeholders consolidated into 11 groups that are engaged across various operational stages and spatial levels. By integrating stakeholder theory and analytical tools such as the Mendelow matrix, the study uncovers underlying power dynamics and significant lock-ins that arise where the emphasis on downstream waste management overshadows preventive upstream measures. The findings highlight the importance of fostering communication and collaboration among stakeholders and creating partnerships within and across stakeholder groups to drive systemic change. Engaging effectively throughout the plastics value chain can pave the way for tailored solutions to local challenges, thereby enhancing sustainability and facilitating alignment with the Sustainable Development Goals. Ultimately, this study advocates for coordinated efforts, ensuring that policy interventions and local actions support a comprehensive, circular approach to effective plastics management.